Conditional cash transfer and the poor : evidence from Bagac and Pilar, Bataan, Philippines - MITZIE IRENE, CONCHADA (Archīum Ateneo, 2016)
The Philippine government launched its poverty program PantawidPamilyang Pilipino Program (4Ps) in 2008 with the goal of assisting poorhouseholds address their short-term needs. Several studies were already donein evaluating the impact of the program on b